ANALISA INTERPRETASI POLA ALIRAN AIR BAWAH TANAH KELURAHAN LABUH BARU BARAT KECAMATAN PAYUNG SEKAKI PEKANBARU MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER - Krisman Krisman; Citra Siti Fatimah Julianti; Juandi M (Universitas Riau, 2019)
Underground water is one of the important component sources for human being. Study on interpretation of underground water flow has been carried out using Geoelectric Schlumberger Electrode Configuration in Labuh Baru Barat Village, Payung Sekaki District, Pekanbaru. The range measurement was chosen to be 240 meter. The output of measurement arecurrent and voltage. The data, then was inputed into software progress and surfer 11. The output of this computer program is a map of underground waterflow pettern and underground lithology. The results of mapping of the pattern of underground water flow indicate that the direction of water flow from North to South direction, or from Pinang street to Payung Sekaki street. The thickness of the layer start from the first layer that is 4.05 meters and 5.4 meters is a layer of silt- clay, the second layer is 13.07 meters and 14.3 meters is a layer of mud stone, the third layer is 13.07 meters and 15.2 meters is a layer of sand and alluvial and the fourth layer is 51.1 meters and 79.2 meters is layer of gravel sand.